Laughing at “normality”: Gerd Brantenberg’s Egalias døtre in translation - Luise von Flotow; Ida Hove Solberg; Enora Lessinger (Lexis: Journal in English Lexicology)
This contribution explores humour as a means of resistance against patriarchal authority in Gerd Brantenberg’s Egalias døtre (1977), a work of feminist science fiction, and its translation into English by Louis Mackay (1985). In this Norwegian gender-bender, humour serves as a facilitator for critical thinking: the coinage of a playful and subversive matriarchal language undermines and ridicules at once the male-as-norm premise that operates in everyday language. This article reflects on the literary tradition the novel belongs to and the key role of lexical creation in the feminist struggle, before analysing the means and effects of lexical creativity in the source text and its translation, from compounding and neologisms to gender-inverting idioms. The results of this contrastive analysis show that the all-important female-as-norm principle at work in the novel, combined with structural differences between source and target languages, lead the translator to make full use of his creative license. By resorting to compensation as a creative translation strategy to create similar effects throughout the novel, he ensures that the English reader also ends up “laughing at patriarchy”, thereby “[breaking] the rules” of patriarchy (Barr [1989: 90-91]).